Illustrated anatomy of the head and neck - Fehrenbach, Margaret J. (Elsevier/Saunders, 2012)
Featuring a robust collection of full-color illustrations and photographs, Illustrated Anatomy of the Head and Neck, 4th Edition, provides a complete look at head and neck anatomy, with an emphasis on the specific anatomy of the temporomandibular joint (TMJ). Chapters are organized by anatomical systems, including one covering the anatomical basis of local anesthesia and another on the spread of dental infection. Written by educators Margaret Fehrenbach and Susan Herring, this edition adds new illustrations and cutting-edge, evidence-based information on topics such as caries risk, periodontal disease, local anesthesia administration, and infection control. Combine this book with Illustrated Dental Embryology, Histology, and Anatomy, and you will gain the basic scientific knowledge needed for everyday clinical dental practice.